2018
DOI: 10.3892/ol.2018.9488
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of curcumin on nude mice bearing lung cancer A549 cell subsets SP and NSP cells

Abstract: Curcumin is a key polyphenolic curcuminoid extracted from the root of turmeric rhizome Curcuma longa Linn, which is a frequently used Chinese herb for the treatment of cancer. The aim of the present study was to investigate the mechanism of the inhibitory effects of curcumin on nude mice with lung cancer A549 cell subsets side population (SP) and non-SP (NSP) cells. BALB/c mice were subcutaneously injected with the tumor cells of A549 SP or NSP subsets consisting of 1x10 9 cells/l (0.2 ml in total). After 16 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…(2015) skin B. senegalensis Elkhateeb et al. (2019) breast, colon C. longa Li et al., 2018 , Li et al., 2018 , Li et al., 2018 ; Coker-Gurkan et al. (2018) ; Li et al., 2018 , Li et al., 2018 , Li et al., 2018 ; Zhao et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2015) skin B. senegalensis Elkhateeb et al. (2019) breast, colon C. longa Li et al., 2018 , Li et al., 2018 , Li et al., 2018 ; Coker-Gurkan et al. (2018) ; Li et al., 2018 , Li et al., 2018 , Li et al., 2018 ; Zhao et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2019) breast, colon C. longa Li et al., 2018 , Li et al., 2018 , Li et al., 2018 ; Coker-Gurkan et al. (2018) ; Li et al., 2018 , Li et al., 2018 , Li et al., 2018 ; Zhao et al. (2018) ; Frassová and Rudá -Kučerová, 2018 ; Arumai Selvan et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a previous study revealed that curcumin liposome exerts antitumor effects by affecting proliferation- and apoptosis-related molecules in rabbits (47). In addition, curcumin inhibits lung cancer growth through the regulation of vascular endothelial growth factor signaling in mice (48). This study demonstrated that curcumin could, to a large extent, block migration, upregulate the expression of E-cadherin and suppress the expression levels of vimentin.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin exhibits its therapeutic potential in lung cancer treatment by acting on the Wnt/β-catenin-dependent pathway in the human lung cancer cell line A549 [ 35 ]. Curcumin also suppresses the vascular endothelial growth factor (VEGF0 and NF-κB expression in the same cell line [ 36 ]. In addition, curcumin has been shown to inhibit the expression of enhancer of zeste homolog 2 (EZH2) in lung cancer cells, which was followed by a decrease in the expression of the Notch 1 gene [ 37 ].…”
Section: Lung Cancermentioning
confidence: 99%